Green synthesis, characterization applications of iron oxide nanoparticles for antialgal and wastewater bioremediation using three brown algae. Issue 14 (6th December 2021) - El-Sheekh, Mostafa M.; El-Kassas, Hala Y.; Shams El-Din, Nihal G.; Eissa, Doria I.; El-Sherbiny, Basma A.
Abstract: This study aims at controlling excess nutrients, including nitrogen and phosphorus, and harmful algae that pollute the marine environment using biosynthesized iron oxide nanoparticles. Aqueous extracts of brown seaweeds named Petalonia fascia, Colpomenia sinuosa, and Padina pavonica were selected for iron oxide nanoparticles' biosynthesis. The extracts were used as reductants of ferric chloride, and dark brown colors due to Fe3 O4 -NPs biosynthesis were observed. Iron signals were recorded in EDX spectra. FTIR analyses showed that the three algae extracts contained proteins and lipids that have the ability to proceed dual functions of bioreduction and stabilization of Fe3 O4 -NPs, suggesting that proteins in P. fascia, C. sinuosa, and P. pavonica extracts reduced FeCl3, and the aromatic compounds stabilized the biogenic Fe3 O4 -NPs. The biosynthesized Fe3 O4 -NPs via P. pavonica had the best nitrogen reduction percentage, followed by C. sinuosa and P. fascia for both concentrations 2 and 4 µg mL −1 . The best results of phosphorus removal and Chlorophyll a (Chl a ) reduction percentages using the Fe3 O4 -NPs concentrations were 2 and 4 µg mL −1 with nanoparticles synthesized via P. fascia and P. pavonica, respectively. The highest reduction in optical density for both 2 and 4 µg mL −1 was achieved by the nanoparticles synthesized by P. fascia. Novelty Statement Application of nanoparticles using seaweeds extracts could be alternative safe bioremediation of wastewaters. Currently, iron oxide nanoparticles are used to reduce nitrogen and phosphorus and reduce the blooming of harmful algae; little information about this issue has been reported. Such study also presented the anti-algal impacts of Fe3 O4 -NPs by tracing optical density and Chl a concentrations in the examined real seawater samples. Modern biotechnology to develop phytoremediation and seaweeds to enhance these remediation methods can be adopted.